2016
DOI: 10.19173/irrodl.v17i2.1913
|View full text |Cite
|
Sign up to set email alerts
|

Issues and Challenges in Open and Distance e-Learning: Perspectives from the Philippines

Abstract: <p class="Style2">Rapid advances in information and communications technology in the digital age have brought about significant changes in the practice of distance education (DE) worldwide. DE practitioners in the Philippines’ open university have coined the term ‘open and distance e-learning’ (ODeL) to refer to the new forms of DE, which are characterised by the convergence of an open learning philosophy, DE pedagogies, and e-learning technologies. This paper discusses the issues and challenges that ODe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 37 publications
1
88
1
2
Order By: Relevance
“…In a related studies, Arinto (2016) and Queiros and de Villiers (2016) agreed, in principle, that three facets need to be in place in order to better prepare both the lecturer and student for online learning:…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In a related studies, Arinto (2016) and Queiros and de Villiers (2016) agreed, in principle, that three facets need to be in place in order to better prepare both the lecturer and student for online learning:…”
Section: Related Workmentioning
confidence: 99%
“…Jung (2017) observed that learner motivation (intrinsic and extrinsic) is crucial to the learners' success in an online coursework environment. JKUAT needs to provide training as it is a way of imparting e-learning skills through training was necessary in order to improve quality (Arinto, 2016;Azawei et al, 2016).…”
Section: Learner Characteristicsmentioning
confidence: 99%
“…For Arinto (2016), these resources are political, administrative, technological, digital, material, financial and human. At the HTTC of Maroua, the administrative resources refer first to the leadership of it managers.…”
Section: Training Programs Target Audience and Resourcesmentioning
confidence: 99%
“…However, when, the formal concept of ontology in the general domain is incompetent, uncertain and ambiguous. So, to describe the fuzzy concept and fuzzy relation of imprecise, uncertain and fuzzy information, fuzzy theory was extended to the ontology [3], and then made it be formed fuzzy ontology, because fuzzy ontology can deal with fuzzy knowledge, and can describe and retrieve text and multimedia objects in the fuzzy information.…”
Section: Introductionmentioning
confidence: 99%